Effect of recovery mode on repeated sprint ability in young basketball players - Castagna, C.; Abt, G.; Manzi, V.; Annino, G.; Padua, E.; D'Ottavio, S. (The Journal of Strength and Conditioning Research, 2008)
The aim of this study was to examine the effect of recovery mode on repeated sprint ability in young basketball players. Sixteen basketball players (age, 16.8 ± 1.2 years; height, 181.3 ± 5.7 cm; body mass, 73 ± 10 kg; VO2max, 59.5 ± 7.9 mL/kg·min) performed in random order over 2 separate occasions 2 repeated sprint ability protocols consisting of 10 × 30-m shuttle run sprints with 30 seconds of passive or active (running at 50% of maximal aerobic speed) recovery. Results showed that fatigue index (FI) during the active protocol was significantly greater than in the passive condition (5.05 ± 2.4, and 3.39 ± 2.3, respectively, p < 0.001). No significant association was found between VO2peak and FI and sprint total time (TT) in either repeated sprint protocols. Blood lactate concentration at 3 minutes post exercise was not significantly different between the 2 recovery conditions. The results of this study show that during repeated sprinting, passive recovery enabled better performance, reducing fatigue. Consequently, the use of passive recovery is advisable during competition in order to limit fatigue as a consequence of repeated high intensity exercise.